Conflict of Interest in Absentee Agricultural Land Ownership by Civil Servants - I Wayan Mustika Eko Yuda; Evita Isretno Israhadi (Syntax Idea)
This research discusses the conflict of interest in absentee agricultural land ownership by Civil Servants (PNS) in Indonesia, which affects land distribution inequality, declining agricultural productivity, and social tensions within the community. In the agrarian context, land ownership by civil servants who do not actively manage their land has the potential to hinder small farmers' access to agrarian resources. This research explores the efforts that can be made to address these conflicts, including regulatory reviews, the implementation of transparency and accountability, community empowerment, and the execution of policies that support sustainable and participatory land management